Postcards from Saddam the true confessions of an economic hitman - Alessandro, Salvatore (Independently published, 2019)
In this riveting memoir, Professor Alessandro recounts how he and his colleagues, all former CIA covert operations officers, didn't bribe foreign officials but used principles of CIA tradecraft, which he now teaches, to negotiate with foreign governments and multi-nationals, and more importantly, to evade capture or imprisonment in hostile countries, including the author?s unexpected encounter with Saddam Hussein while traveling without the Italian passport he normally used to conceal his American identity.
Keywords: Imperialism